Thesaurus of Indonesian Islamic Manuscripts (T2IM): An Effort to Develop a Comprehensive Database for Academic Purpose - Oman Fathurahman (Studia Islamika, 2009)
As stated above, one of T2IM's main objectives is to provide information and data as complete as possible concerning Indonesian religious manuscripts. In order to achieve this target, T2IM needs to be systematically improved. Until now, Indonesian manuscripts are largely kept in private and public institutions including libraries, museums, and foundations, both in Indonesia and abroad. Some manuscripts collections have been catalogued, however, most of them have not. Initially, T2IM will draw upon printed catalogues as well as other lists of manuscripts and on other documentation. All publications containing lists of Indonesian religious manuscripts, whether they provide complete information or only titles, will be included in T2IM's database.DOI: 10.15408/sdi.v16i3.479